ANALISIS PERANCANGAN KEMBALI SISTEM PENYEDIAAN AIR BERSIH DI DESA GIRICAHYO KECAMATAN PURWOSARI KABUPATEN GUNUNGKIDUL DI YOGYAKARTA BERBASIS HOMER - , NASHRIL ABDILLAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Water Supply System in Giricahyo Village was built in 2007. This system was powered from generator 30 kW and PV 12 kWp, but the system is stand alone and disjointed. Generator is used to drive 1 pump while PV pumps 10 submersible pumps and arranged in two pumping sistems with a total of head 235 m. Both of these systems did not work since 2010. Ministry of Public Work through Unit Department of PK-PAM Yogyakarta wants to repair the system back. In collaboration with the Department of Physics Engineering UGM, the research was conducted to evaluate and re design water supply system. This study specifically focused on re-design based on HOMER software. The result of this study is a recommendation and analysis sistem performed using HOMER. HOMER analyzes performance using deferrable and primary loads methods. This analysis sees how far the prospects of PV energy can be used as well as determines the optimal pump power that can be used by making variable of its pump. The result, 12 kWp PV needed converter 4 kW to meet the needs of optimum of 31.4 %. Pump load are 1.5 kW and 3 kW load used in the primary method analysis. As a result, capacity shortage of 1.5 kW is at 3.2 % and for 3 kW pump is at 9.9 % which means the use of pumps up to 1.5 kW is better and can deal with fluctuating solar radiation. The demand that can be fulfilled by 1.5 kW pump is at 22.4 % . The use of generators is not recommended.